(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This paper deals briefly with the slave trade in Sudan which suffered for a long time because of the involvement of its local leaders with other Africans and Europeans in this trade humanity especially during this period. The meaning of slavery first defined and its types,and position of Islam, which was manifested in the issuance of a number of judgments based on the book of Allah and Sunnah of his Messenger in order to liberate the slave and prevent their penetration , explaining the main sources and ways to obtain it, this study was also investigated in the treatment of slavery and trading them, in addition to the study examined the role of the Egyption government and the efforts it exerted to combat this trade and cancel its abolition in the era of Mohamed Ali Pasha and his successors with the most important effects and consequences.